2008
DOI: 10.1523/jneurosci.1905-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Profiles of Field Potentials in Mouse Superior Colliculus Analyzed by Multichannel Recording

Abstract: The onset and vector of orienting behaviors, such as saccades, are controlled by commands that descend from a population of neurons in deep layers of the superior colliculus (dSC). In this study, to characterize the role of the collicular local circuitry that generates the spatiotemporal pattern of command activity in the dSC neuronal population, responses evoked by single-pulse electrical stimulation in superficial layers of the superior colliculus (sSC) were analyzed by a 64-channel field potential recording… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 43 publications
(50 reference statements)
1
20
0
Order By: Relevance
“…The faint blue regions in the SGI and deep layers (Fig. 12 C,G ) indicate that GABA A receptors ordinarily limit the spread of activity into this region, consistent with recent reports (Saito and Isa, 2003; Phongphanphanee et al, 2008; Isa and Hall, 2009). Quantitative analyses of drug effects on mediolateral and dorsoventral spread are described in detail below (Figs.…”
Section: Resultssupporting
confidence: 91%
“…The faint blue regions in the SGI and deep layers (Fig. 12 C,G ) indicate that GABA A receptors ordinarily limit the spread of activity into this region, consistent with recent reports (Saito and Isa, 2003; Phongphanphanee et al, 2008; Isa and Hall, 2009). Quantitative analyses of drug effects on mediolateral and dorsoventral spread are described in detail below (Figs.…”
Section: Resultssupporting
confidence: 91%
“…In addition, s-ketamine also blocks NMDA receptors within the Superior Colliculi of the mid-brain (SC; cf. Dumanskaya, Kosheleva, & Veselovsky, 2012;Phongphanphanee, Kaneda, & Isa, 2008; see also Grossberg, Roberts, http Aguilar, & Bullock, 1997). The SC also play an active role in shifting visual attention, steering saccades, and inhibiting of attention shifts back to a previously attended (or cued) position (Dorris, Klein, Everling, & Munoz, 2002;Everling, Dorris, Klein, & Munoz, 1999;Fecteau, Bell, & Munoz, 2004;Sapir, Soroker, Berger, & Henik, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In the SC of the rat, Binns and Salt (1997) showed that GABA reduces responses of superficial gray neurons to visual stimuli and is important for surround inhibition in vivo. In vitro, disinhibition enhanced response amplitudes in the avian TeO (Dye and Karten 1996) or the SC (Özen et al 2000;Phongphanphanee et al 2008;Saito and Isa 2003;Vokoun et al 2010) and increased the active area (Phongphanphanee et al 2008;Vokoun et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Previous in vitro work has shown that neuronal responses in the TeO and the SC are highly regulated by GABA release. Disinhibition by GABA A receptor blockers usually enhanced signal amplitudes in whole cell or extracellular recordings (Dye and Karten 1996; Özen et al 2000;Phongphanphanee et al 2008;Saito and Isa 2003) and in optical imaging recordings of the SC (Vokoun et al 2010). In the SC, it also altered the spatial distribution (Phongphanphanee et al 2008;Vokoun et al 2010).…”
Section: Characteristics Of Voltage Imaging Responsementioning
confidence: 99%
See 1 more Smart Citation